2((x+2)(x+2)}-4=28
2{x^2 + 4x + 4}-4=28
2x^2 +4x=28
2(x^2+2x)=28
x^2+2x=28/2
x^2+2x=14
Answer:
Option C ![10+5x=24+3x](https://tex.z-dn.net/?f=10%2B5x%3D24%2B3x)
Step-by-step explanation:
Let
x ------> the cost of each shirt
we know that
The cost of 5 shirts plus $10 (amount of money that would remain) must be equal to the cost of 3 shirts plus $24 (amount of money that would remain). Considering that the cost of the shirts is the same
The linear equation that represent this scenario is
![10+5x=24+3x](https://tex.z-dn.net/?f=10%2B5x%3D24%2B3x)
Solve for x
![5x-3x=24-10](https://tex.z-dn.net/?f=5x-3x%3D24-10)
![2x=14](https://tex.z-dn.net/?f=2x%3D14)
![x=\$7](https://tex.z-dn.net/?f=x%3D%5C%247)
Answer:The average rate of change between two input values is the total change of the function values (output values) divided by the change in the input values.
Step-by-step explanation:
Answer:
Step 1: Determine the prime factors of the number under the root. Step 2: Write the prime factors in groups. Step 3: Simplify any multiplication and exponents. Step 4: Simplify the radical until no further simplification can be done.
Step-by-step Have explanation:
a great day
Minus 5 from both sides so we have 3a=-19 now divide both sides by 3 so we have a=-6 1/3